(untitled) (Medico Legal Update, 2021)
For centuries, autopsy has been instrumental in establishing the cause of death both in clinical and forensic cases. Even though it helps in arriving at a decision regarding the cause of death and many other things, its use is declining recently, which should be a cause of concern. With this background, the present study has been carried out in January 2020 on 150 medical students of 2nd year MBBS by using set of questionnaires, to assess their knowledge and attitude towards autopsy at department of Forensic Medicine and Toxicology at BVDU & MC, Sangli, Maharashtra. This study shows the students had a reasonable knowledge and good attitude towards medico-legal autopsy. Majority of the students agreed that need of autopsy in all unnatural, sudden, unexpected and suspicious death is mandatory and collection of viscera for histo-pathological and toxicological analysis is useful. Majority of the students think that autopsy helps in solving crimes and gives information to police. Most of the study population shows interest in attending and performing a greater number of autopsies. Majority of the students agreed that post mortem examination is useful in medical education. Majority of the study population says that autopsy is disrespect to human body. Most of the study population is not aware of virtual autopsy